Kecemasan Politik sebagai Bagian dari Proses Pembelajaran Kewarganegaraan serta Partisipasi Mahasiswa di Pendidikan Tinggi: Political Anxiety as Part of the Civic Learning Process and Student Participation in Higher Education - Leoni Diastanti; Siti Jaro'ah (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Student political participation is an important indicator of the success of civics learning in higher education, as it reflects students’ ability to understand and respond to public issues. However, increasingly complex political dynamics and the intensity of exposure to digital information in the learning process contribute to the emergence of political anxiety among students. In Indonesia, studies on student political participation have predominantly emphasized cognitive aspects, such as political literacy and political efficacy, while the role of emotional experiences in civics learning remains underexplored. Yet, political emotions have the potential to shape how students interpret political issues and determine the forms of their involvement. This study employed a quantitative approach with a cross-sectional survey design. The participants were 230 undergraduate students aged 18–25 in Surabaya, selected through purposive sampling. Data were collected online using instruments measuring political anxiety and political participation. Data analysis was conducted using simple linear regression to examine the effect of political anxiety on student political participation. The results indicate that political anxiety has a positive and significant effect on student political participation. Political anxiety explains part of the variation in students’ political participation, while other factors related to educational experiences also play a role. These findings suggest that political anxiety is not always a barrier but can function as a catalyst for student political participation. In the context of higher education, political anxiety constitutes an integral component of the civic learning experience, encouraging information-seeking behavior, academic discussion, and critical reflection on public issues. Higher education institutions therefore play a strategic role in managing students’ emotional experiences to ensure that political participation develops in a reflective and responsible manner.